Revisiting Chinese Indonesian Violence in Indonesian Post-New Order Fiction (KEMANUSIAAN The Asian Journal of Humanities, 2024)
May 1998 saw one of the worst cases of racial violence in Indonesian history. During 13th to 15th May 1998, there were acts of expropriation, looting, arson and sexual assault targeting the Chinese community in Indonesia. Using two specimens of Indonesian post-New Order fiction, Sekuntum Nozomi 3 (SN3) by Marga Tjoa and Putri Cina (PC) by Sindhunata, this study investigates how cultural memories of the May 1998 Tragedy were shared with the post-event generation. The method employed is a qualitative narrative with a narratological approach. The results showed that literary works function as a medium for the spread of memory. Through SN3 and PC, the memory of violence against ethnic Chinese Indonesians between 12th and 15th May 1998 is transmitted, especially for the post-event generation who did not experience it firsthand. Despite the differing representation strategy, there was substantively one voice to be conveyed, namely that of “discrimination, violence and human rights violations” against Chinese Indonesians. Memories are institutionalised and distributed as part of the national memory in these works. Both works mediate the politics of cultural memory to memorialise the past “sins” of the Indonesian people. These literary works can be viewed as tools for minorities to articulate discrimination.